Esensi Maqashid Syari ‘ah dalam Kurikulum dan Pembelajaran Fiqih - Afifah, Nurul (Tapis: Jurnal Penelitian Ilmiah, 2017)
Maqashid Sharia is the purpose of Allah Swt, as syar'iah maker to give the benefit of his servant, both in this world and in the hereafter when they acting accordance with the rules of the Shari'ah Allah.In the curriculum, wich includes materials jurisprudence of the reasons why someone must worship according to Islamic law, what is the purpose and benefit to them is maqashid al-Sharia. Jurisprudence based material maqashid al-Sharia will emphasize why the students should worship, what are the benefits, uses, benefits and wisdom for them. Knowing maqashid Sharia, students will be motivated to perform worship that was taught by sincere, foster a sense of obedience to Allah and to develop awareness of themselves in religious practice in everyday life. The effective and efficient of concept learning that is delivering materials maqashid Sharia-based jurisprudence, namely the principles of learning utilizes brain potential students, grow the insight or perception of the students, emotions, putting the procedural capabilities, meaningfull learning, and learning by fun. The strategy used collaboration of inquiry learning, contextual and expository, lectures method, story telling, demonstrations, resource person, recitation and questioning. Media studies; visual, audio, visual and audio environment. Learning resources are books, magazines, newsletters, the Internet, and bring in natural resources (actors). Evaluation adheres to the principle of continuity, integrity and holistic.